Problematika Pembelajaran Sejarah Sastra di Kampus Wilayah Perbatasan Negara Kesatuan Republik Indonesia-Republik Demokratik Timor Leste - Uman Rejo (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This research aims to explore and describe some of the problems experienced in the learning History of Literature courses in Indonesian Language and Literature Education courses on the campus of the border region of the Unitary State of the Republic of Indonesia-Democratic Republic of Timor Leste (NKRI-RDTL). One of the campuses located in the border area is the University of Timor (Unimor). The problems explored will be balanced with several solutions and recommendations, to reduce some of the problems represented. In this case, the method used is a qualitative descriptive method using an e-ethical paradigm. This paradigm was used by Clifford Geertz in The Religion of Java which was presented to Abangan Santri dan Priyayi dalam Masyarakat Jawa (1981) by Aswab Mahasin. About Timorese culture, Gregor Neonbasu applied this paradigm in his monograph entitled Citra Manusia Berbudaya: Sebuah Monografi tentang Timor dalam Perspektif Melanesia (2017). The subject of this research is the study activity learning History of Literature inactive students of the first semester (odd) study program of Indonesian Language and Literature Education Faculty of Educational Sciences, University of Timor academic year 2019—2020. Based on the results of the study concluded that the problem faced in the learning History of Literature courses on the campus of the border area of NKRI-RDTL is due to five aspects, namely material aspects or teaching materials, methods, media, students, and literacy.